Titanium-doped carbon fiber negative electrode material and preparation method thereof

By combining graphite powder with carbon fiber and dispersing titanium dioxide particles in the shell structure, the titanium-doped carbon fiber negative electrode material is prepared, and the conductivity and cost problems of the carbon fiber negative electrode material are solved, the conductivity and cyclic performance of the material are improved, and the specific capacity and energy density of the negative electrode are enhanced.

CN120565611AActive Publication Date: 2025-08-29展长振
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510634677.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-08-29
Estimated Expiration
2045-05-16

AI Technical Summary

Technical Problem

The existing carbon fiber negative electrode materials have weak conductivity and high cost, making it difficult to promote and apply in various fields.

Method used

By combining graphite powder with carbon fibers, a core-shell structure is formed, and the titanium-doped carbon fiber negative electrode material is uniformly dispersed in the shell structure to improve conductivity and lithium embedded space.

Benefits of technology

The conductivity and cyclic performance of the negative electrode material are improved, the cost is reduced, and the specific capacity and energy density of the negative electrode are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005406337920000111
    Figure BDA0005406337920000111
Patent Text Reader

Abstract

The invention discloses a preparation method of a titanium-doped carbon fiber negative electrode material, which comprises the following steps: intercalating graphite, compounding with carbon fiber, and sequentially carrying out carbon coating, carbonization and crushing to obtain the negative electrode material. The intercalated graphite is compounded with the carbon fibers through physical adsorption, so that the conductivity is improved, the use amount of the carbon fibers can be reduced, and the cost is reduced. The particle size of the graphite is very small, the defects of the carbon fibers can be overcome through the adsorption process, volume support is provided for the carbon fibers in the charge-discharge process, stress generated during deformation of the carbon fibers is dispersed, a core-shell structure is formed through carbon coating, expansion and shrinkage of the core structure are further limited, and the cycle performance is improved. And titanium dioxide is uniformly dispersed in the coating liquid, so that titanium dioxide particles are uniformly distributed on the shell structure, and titanium dioxide has a relatively large interlayer spacing structure and can be used as a lithium ion transmission interface, so that the first coulombic efficiency of the material is improved, the lithium intercalation capacity of the shell material can be improved, and the specific capacity and the energy density of the negative electrode are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode materials, and in particular to a titanium-doped carbon fiber negative electrode material and a preparation method thereof. Background Art

[0002] The main reason for the volume change of the negative electrode of a lithium battery is due to the embedding and extraction of lithium ions during the charging and discharging process. During charging, lithium ions are embedded from the positive electrode into the negative electrode, causing the volume of the negative electrode material to expand; while during discharging, lithium ions are extracted from the negative electrode and returned to the positive electrode, causing the volume of the negative electrode material to shrink accordingly. This volume change is caused by the change in the lattice structure caused by the embedding and extraction of lithium ions, and it will affect the capacity and cycle stability of the battery, causing the battery performance to gradually decline. In order to improve battery performance, some manufacturers use carbon fiber negative electrode materials to manufacture the negative electrode of lithium batteries. During the charging and discharging process, the volume change of carbon fiber negative electrode materials is small, which can significantly extend the cycle life of the battery.

[0003] However, carbon fiber has relatively weak conductivity and high cost, making it difficult to promote its application in various fields. Therefore, it is necessary to improve the existing carbon fiber negative electrode materials. Summary of the Invention

[0004] In view of this, the present invention addresses the deficiencies in the prior art, and its main purpose is to provide a titanium-doped carbon fiber negative electrode material and a preparation method thereof, which can effectively solve the problems of the existing carbon fiber negative electrode materials having relatively weak conductivity, high cost, and difficulty in promoting and applying them in various fields.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a titanium-doped carbon fiber negative electrode material comprises the following steps:

[0007] (1) mixing graphite powder with an intercalating agent and an oxidant and performing an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:(1-5):(0.05-0.5), the reaction temperature is 40° C., and the reaction time is 10-40 min to obtain intercalated graphite powder;

[0008] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 10-60 seconds to obtain expanded graphite;

[0009] (3) after cooling the expanded graphite obtained in step (2) to room temperature, transferring it to an inert gas atmosphere, heating it to 2500° C. at a heating rate of 50-90° C. / h, and keeping it warm for 1-3 h to obtain conductive graphite;

[0010] (4) placing the conductive graphite and carbon fiber obtained in step (3) in acetone at a mass ratio of (1-3):1, ultrasonicating for 1-5 hours, and drying to obtain a graphite-carbon fiber composite material;

[0011] (5) placing titanium dioxide and asphalt in ethanol and dispersing them uniformly to obtain a coating liquid, and then placing the graphite-carbon fiber composite material obtained in step (4) in the coating liquid and heating and stirring it, wherein the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is (10-100): (1-5): (1-10), the stirring rate is 50-150 rpm, the stirring temperature is 30-50°C, and the stirring is carried out until the ethanol is evaporated to obtain a coating;

[0012] (6) The coated material obtained in step (5) is placed in a reactor and carbonized in an inert gas atmosphere at a carbonization temperature of 800-1000° C. for 4-6 hours. After cooling, the material is crushed to obtain a negative electrode material.

[0013] As a preferred embodiment, the intercalation agent in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid.

[0014] As a preferred embodiment, the oxidant in step (1) is ammonium persulfate.

[0015] As a preferred solution, the ultrafine graphite in step (1) is ultrafine flake graphite, with D10 = 0.05 μm, D50 = 0.16 μm, and D90 = 0.5 μm.

[0016] As a preferred embodiment, the inert gas in step (3) and step (6) is argon.

[0017] As a preferred embodiment, the asphalt in step (5) is petroleum asphalt or coal asphalt.

[0018] As a preferred embodiment, the titanium dioxide in step (5) is nano-scale titanium dioxide (B).

[0019] A titanium-doped carbon fiber negative electrode material is prepared by the above-mentioned method for preparing the titanium-doped carbon fiber negative electrode material.

[0020] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0021] The intercalated graphite is compounded with carbon fiber through physical adsorption to improve conductivity, reduce the amount of carbon fiber used, and reduce costs. The particle size of graphite is very small, and it can be adsorbed to fill the defects of carbon fiber. During the charge and discharge process, graphite provides resistance to the volume reduction of carbon fiber, disperses the stress generated when the carbon fiber is deformed, and then cooperates with carbon coating to form a core-shell structure, further limiting the expansion and contraction of the core structure and improving the cycle performance; and titanium dioxide is evenly dispersed in the coating liquid, so that titanium dioxide particles are evenly distributed on the shell structure. Titanium dioxide has a large interlayer structure, which effectively increases the lithium insertion space and increases the lithium insertion capacity of the shell material, thereby increasing the specific capacity and energy density of the negative electrode.

[0022] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below with reference to specific embodiments. DETAILED DESCRIPTION

[0023] The present invention discloses a method for preparing a titanium-doped carbon fiber negative electrode material, comprising the following steps:

[0024] (1) mixing graphite powder with an intercalating agent and an oxidant and performing an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:(1-5):(0.05-0.5), the reaction temperature is 40°C, and the reaction time is 10-40 minutes to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0025] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 10-60 seconds to obtain expanded graphite.

[0026] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 50-90° C. / h, and kept warm for 1-3 h to obtain conductive graphite.

[0027] (4) placing the conductive graphite and carbon fiber obtained in step (3) in acetone at a mass ratio of (1-3):1, ultrasonically treating for 1-5 hours, and drying to obtain a graphite-carbon fiber composite material.

[0028] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is (10-100): (1-5): (1-10), the stirring rate is 50-150 rpm, the stirring temperature is 30-50°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is petroleum asphalt or coal asphalt, and the titanium dioxide is nano-scale titanium dioxide (B).

[0029] (6) The coated material obtained in step (5) is placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 800-1000° C. for 4-6 hours. After cooling, the material is crushed to obtain a negative electrode material.

[0030] The present invention also discloses a titanium-doped carbon fiber negative electrode material, which is prepared by the above-mentioned preparation method of the titanium-doped carbon fiber negative electrode material.

[0031] The following is an analysis based on specific examples.

[0032] Example 1

[0033] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:1:0.3, the reaction temperature is 40° C., and the reaction time is 30 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0034] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 30 seconds to obtain expanded graphite.

[0035] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 50° C. / h, and kept warm for 2 h to obtain conductive graphite.

[0036] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of conductive graphite to carbon fiber of 2:1, ultrasonicated for 3 hours, and dried to obtain a graphite-carbon fiber composite material.

[0037] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred. The mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 50:2:10, the stirring rate is 100 rpm, the stirring temperature is 30°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is coal tar, and the titanium dioxide is nano-scale titanium dioxide (B).

[0038] (6) The coated material obtained in step (5) was placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 800° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0039] Example 2

[0040] (1) Mixing graphite powder with an intercalating agent and an oxidant and performing an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:3:0.05, the reaction temperature is 40° C., and the reaction time is 10-40 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0041] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 60 seconds to obtain expanded graphite.

[0042] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 60° C. / h, and kept warm for 3 h to obtain conductive graphite.

[0043] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of the conductive graphite to the carbon fiber of 2.5:1, ultrasonicated for 1.5 hours, and dried to obtain a graphite-carbon fiber composite material.

[0044] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 10:5:1, the stirring rate is 50 rpm, the stirring temperature is 50°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is petroleum asphalt, and the titanium dioxide is nano-scale titanium dioxide (B).

[0045] (6) The coated material obtained in step (5) is placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 900° C. for 5 h. After cooling, the material is crushed to obtain a negative electrode material.

[0046] Example 3

[0047] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:5:0.2, the reaction temperature is 40° C., and the reaction time is 10 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0048] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 10 seconds to obtain expanded graphite.

[0049] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 90° C. / h, and kept warm for 3 h to obtain conductive graphite.

[0050] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of the conductive graphite to the carbon fiber being 1:1, ultrasonicated for 4 hours, and dried to obtain a graphite-carbon fiber composite material.

[0051] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 100:4:8, the stirring rate is 100 rpm, the stirring temperature is 45°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is petroleum asphalt, and the titanium dioxide is nano-scale titanium dioxide (B).

[0052] (6) The coated material obtained in step (5) is placed in a reactor and carbonized under an argon atmosphere at a temperature of 850° C. for 6 h. After cooling, the material is crushed to obtain a negative electrode material.

[0053] Example 4

[0054] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:5:0.5, the reaction temperature is 40° C., and the reaction time is 25 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0055] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it at that temperature for 50 seconds to obtain expanded graphite.

[0056] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 55° C. / h, and kept warm for 1 h to obtain conductive graphite.

[0057] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of conductive graphite to carbon fiber of 2:1, ultrasonicated for 5 hours, and dried to obtain a graphite-carbon fiber composite material.

[0058] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 25:1:1, the stirring rate is 80 rpm, the stirring temperature is 35°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is petroleum asphalt, and the titanium dioxide is nano-scale titanium dioxide (B).

[0059] (6) The coated material obtained in step (5) is placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 900° C. for 4 h. After cooling, the material is crushed to obtain a negative electrode material.

[0060] Example 5

[0061] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:3:0.3, the reaction temperature is 40° C., and the reaction time is 40 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0062] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 35 seconds to obtain expanded graphite.

[0063] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 70° C. / h, and kept warm for 2.5 h to obtain conductive graphite.

[0064] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of conductive graphite to carbon fiber of 3:1, ultrasonicated for 5 hours, and dried to obtain a graphite-carbon fiber composite material.

[0065] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 100:4:7, the stirring rate is 150 rpm, the stirring temperature is 45°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is coal tar, and the titanium dioxide is nano-scale titanium dioxide (B).

[0066] (6) The coated material obtained in step (5) was placed in a reactor and carbonized under an argon atmosphere at a temperature of 880° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0067] Example 6

[0068] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:3:0.35, the reaction temperature is 40° C., and the reaction time is 30 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0069] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 60 seconds to obtain expanded graphite.

[0070] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 90° C. / h, and kept warm for 3 h to obtain conductive graphite.

[0071] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of conductive graphite to carbon fiber of 2.6:1, ultrasonicated for 1 hour, and dried to obtain a graphite-carbon fiber composite material.

[0072] (5) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then the graphite-carbon fiber composite material obtained in step (4) is placed in the coating liquid and heated and stirred, the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is 30:3:2, the stirring rate is 70 rpm, the stirring temperature is 30°C, and the stirring is carried out until the ethanol evaporates completely to obtain a coating; the asphalt is petroleum asphalt or coal asphalt, and the titanium dioxide is nano-scale titanium dioxide (B).

[0073] (6) The coated material obtained in step (5) was placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 1000° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0074] Comparative Example 1

[0075] (1) Titanium dioxide and asphalt are placed in ethanol and dispersed evenly to obtain a coating liquid, and then carbon fiber is placed in the coating liquid and heated and stirred. The mass ratio of carbon fiber to titanium dioxide and asphalt is 50:2:10, the stirring rate is 100 rpm, and the stirring temperature is 30°C. Stirring is carried out until the ethanol evaporates completely to obtain a coating; the asphalt is coal tar, and the titanium dioxide is nano-sized titanium dioxide (B).

[0076] (2) The coated material obtained in step (1) was placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 800° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0077] Comparative Example 2

[0078] (1) The carbon fiber is placed in asphalt and heated and stirred. The mass ratio of the carbon fiber to the asphalt is 50:12. The stirring rate is 100 rpm and the stirring temperature is 30°C. The stirring is continued until the ethanol evaporates completely to obtain a coating. The asphalt is coal tar.

[0079] (2) The coated material obtained in step (1) was placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 800° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0080] Comparative Example 3

[0081] (1) Graphite powder is mixed with an intercalating agent and an oxidant and subjected to an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:1:0.3, the reaction temperature is 40° C., and the reaction time is 30 min to obtain intercalated graphite powder; the ultrafine graphite is ultrafine flake graphite with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm, the intercalating agent is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is ammonium persulfate.

[0082] (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 30 seconds to obtain expanded graphite.

[0083] (3) After the expanded graphite obtained in step (2) is cooled to room temperature, it is transferred to an argon atmosphere, heated to 2500° C. at a heating rate of 50° C. / h, and kept warm for 2 h to obtain conductive graphite.

[0084] (4) The conductive graphite and carbon fiber obtained in step (3) are placed in acetone with a mass ratio of conductive graphite to carbon fiber of 2:1, ultrasonicated for 3 hours, and dried to obtain a graphite-carbon fiber composite material.

[0085] (5) The graphite-carbon fiber composite material obtained in step (4) is placed in asphalt and heated and stirred. The mass ratio of the graphite-carbon fiber composite material to the asphalt is 50:12, the stirring rate is 100 rpm, the stirring temperature is 30°C, and the stirring is carried out until the ethanol is completely evaporated to obtain a coating; the asphalt is coal tar.

[0086] (6) The coated material obtained in step (5) was placed in a reactor and carbonized under an argon atmosphere at a carbonization temperature of 800° C. for 4.5 h. After cooling, the material was crushed to obtain a negative electrode material.

[0087] Performance tests were conducted on the above-mentioned embodiments and comparative examples, and the test results are shown in Table 1. The data were obtained by testing button-type half-cells.

[0088]

[0089] Table 1

[0090] It can be clearly seen from the above data that the negative electrode material prepared using the preparation method of the present invention has excellent specific capacity, initial efficiency and capacity retention rate. Compared with Example 1, the specific capacity and initial efficiency of Example 1 are slightly inferior to those of Example 1, but after 300 cycles, the capacity retention rate is significantly inferior to that of Example 1. The reason is that in Example 1, there is no defect of ultra-small particle size graphite used to fill carbon fibers. During the charge and discharge process, the volume change of the electrode cannot be effectively suppressed, resulting in a relatively poor capacity retention rate. Compared with Example 2, Example 1 has an initial efficiency worse than that of Example 1, and its cycle performance is much worse than that of Example 1. This is mainly due to the lack of graphite to maintain structural stability and the lack of a stable ion transfer interface provided by titanium dioxide. After 300 cycles, the capacity retention rate is only 88.5%. Compared with Example 1 and Comparative Example 3, Example 3 lacks titanium dioxide doping, and the initial efficiency is significantly reduced. Although the capacity can still be maintained at a relatively good level, the shell structure lacks the stable ion transmission interface provided by titanium dioxide, so that after 300 cycles, the capacity retention rate of Comparative Example 3 decreases more significantly than that of Comparative Example 1.

[0091] The above description is merely a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any minor modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a titanium-doped carbon fiber negative electrode material, characterized in that: The following steps are included: (1) mixing graphite powder with an intercalating agent and an oxidant and performing an oxidative intercalation reaction, wherein the graphite powder is ultrafine graphite, the mass ratio of the graphite powder to the intercalating agent and the oxidant is 1:(1-5):(0.05-0.5), the reaction temperature is 40° C., and the reaction time is 10-40 min to obtain intercalated graphite powder; (2) drying the intercalated graphite powder obtained in step (1), and then rapidly heating it to 1000° C. and keeping it warm for 10-60 seconds to obtain expanded graphite; (3) after cooling the expanded graphite obtained in step (2) to room temperature, transferring it to an inert gas atmosphere, heating it to 2500° C. at a heating rate of 50-90° C. / h, and keeping it warm for 1-3 h to obtain conductive graphite; (4) placing the conductive graphite and carbon fiber obtained in step (3) in acetone at a mass ratio of (1-3):1, ultrasonicating for 1-5 hours, and drying to obtain a graphite-carbon fiber composite material; (5) placing titanium dioxide and asphalt in ethanol and dispersing them uniformly to obtain a coating liquid, and then placing the graphite-carbon fiber composite material obtained in step (4) in the coating liquid and heating and stirring it, wherein the mass ratio of the graphite-carbon fiber composite material to titanium dioxide and asphalt is (10-100): (1-5): (1-10), the stirring rate is 50-150 rpm, the stirring temperature is 30-50°C, and the stirring is carried out until the ethanol is evaporated to obtain a coating; (6) The coated material obtained in step (5) is placed in a reactor and carbonized in an inert gas atmosphere at a carbonization temperature of 800-1000° C. for 4-6 hours. After cooling, the material is crushed to obtain a negative electrode material.

2. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The intercalation agent in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid.

3. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The oxidant in step (1) is ammonium persulfate.

4. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The ultrafine graphite in step (1) is ultrafine flake graphite, with D10=0.05 μm, D50=0.16 μm, and D90=0.5 μm.

5. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The inert gas in step (3) and step (6) is argon.

6. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The asphalt in step (5) is petroleum asphalt or coal asphalt.

7. The method for preparing the titanium-doped carbon fiber negative electrode material according to claim 1, characterized in that: The titanium dioxide in step (5) is nano-scale titanium dioxide (B).

8. A titanium-doped carbon fiber negative electrode material, characterized by: The titanium-doped carbon fiber negative electrode material is prepared by the preparation method of the titanium-doped carbon fiber negative electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Composite carbon fiber

    CN103523766A

  • Preparation method of titanium dioxide composite carbon nano-fiber negative material of lithium ion battery

    CN104022260A

  • Application of micro-expanded graphite material

    CN104140098A

  • Nanometer silicon particle-graphite flake-carbon nanotube composite material and preparation method and application thereof

    CN105226254A

  • High-capacity TiO2-VO2 doped hollow carbon nanofiber lithium battery negative electrode material and preparation method thereof

    CN108346787A